The potential use of rhizobacteria and cover crop residue for improving the growth of sorghum on post-nickel mining soil in Southeast Sulawesi - Leomo, Sitti; Alam, Syamsu; Muhidin; Sadimantara, Gusti R (Journal of Degraded and Mining Lands Management, 2025)
The utilization of rhizobacteria and cover crop residue for improving plant productivity has been widely applied in agricultural land. However, the effectiveness of those treatments for increasing the growth performance of crops in the post-mining soil is still not evaluated. This study investigated the potential use of rhizobacteria and cover crop residue for improving the growth of Sorghum sp. developed in the post-mining soil in Southeast Sulawesi. An experiment was established at the laboratory level using a completely randomized design with three replicates for every treatment. Four treatments were examined in this trial comprising of CE (control+Eleusine indica), CC (control+Centrosema sp.), BE (Bacillus sp.+Eleusine indica), and BC (Bacillus sp.+Centrosema sp.). Some parameters were observed to evaluate the growth of Sorghum sp., namely diameter, height, total leaves, leaf area, and biomass. The results demonstrated the use of rhizobacteria and cover crop residue potentially improves the growth of Sorghum sp. in the post-mining soil even though there was not a significant difference among treatments statistically. The highest average biomass of Sorghum sp. was noted in BE (3.72±1.06 g), BC (3.20±0.50 g), CC (2.95±1.40 g), CE (2.81±0.33 g). These findings indicated that the treatment of BE was the best way to improve the growth performance of Sorghum sp. at the post-mining. According to the results, this study concluded that rhizobacteria and cover crops play a key role in soil fertility. The utilization of rhizobacteria and cover crop residue has the potential to support the growth of Sorghum sp. developed in the post-nickel mining soil.